Smart room energy tracker automated electrical usage calculator for individual house - Aziz, Muhammad Azim; Ahmad, Nur Azfahani (2024)
Manual tracking methods that are time-consuming and lack detailed insights often impede energy management in modern houses. The Smart Room Energy Tracker addresses these challenges by providing a comprehensive platform for analysing electrical consumption on a room-by-room basis using Excel. This innovation leverages existing energy formulas to offer detailed insights into energy usage patterns, which are essential for effective energy management. The methodology involves user data entry, automated calculations, and detailed analysis, including pie and bar charts, to visualise energy performance. Results show a significant improvement in energy management, with the system enabling precise identification of high-consumption areas and facilitating targeted energy-saving measures. The Smart Room Energy Tracker enhances energy efficiency, supports informed decision-making, and improves overall household comfort. The system's commercial potential lies in its ability to provide cost-saving benefits, promote sustainability, and optimise energy use through quick and clear analysis.